2016 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM) 2016
DOI: 10.1109/ieem.2016.7797877
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian anthropometry update through Drillis & Contini revisited and Structural Equation Modeling incorporating children, adult and elderly populations

Abstract: to all population groups, both for male and female subjects. Moreover, it was confirmed that the ratio scale method has been sufficiently applied to all anthropometric groups, so that the body segments measures can be predicted. Practically, the finding can be utilized to support product design and development phases, especially in the use of more appropriate anthropometric data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The first factor included the dimensions 1 to 11,13,14,17,18,22,23,24,25,28,30,32,33,34,35 and 36, which were related to limb segment, while the second factors consisted of dimensions 12, 15, 19, 20, 21, 26, 27, 29 and 31. This finding confirmed the generic model of the relationship between limb segment and stature, and girth/width segment and weight, respectively (see Peacock et al, 2012;Hartono, 2016).…”
Section: Empirical Prediction Of Anthropometric Dimensions Using Drilsupporting
confidence: 83%
See 2 more Smart Citations
“…The first factor included the dimensions 1 to 11,13,14,17,18,22,23,24,25,28,30,32,33,34,35 and 36, which were related to limb segment, while the second factors consisted of dimensions 12, 15, 19, 20, 21, 26, 27, 29 and 31. This finding confirmed the generic model of the relationship between limb segment and stature, and girth/width segment and weight, respectively (see Peacock et al, 2012;Hartono, 2016).…”
Section: Empirical Prediction Of Anthropometric Dimensions Using Drilsupporting
confidence: 83%
“…This study involved more than 600 Sundanese children anthropometric data (aged 6e9 years) in determining the clothing size. Moreover, study by Hartono (2016) which involved more than 400 subjects has found that limb segment and girth/width segment have a significant correlation with stature and body weight, respectively, through structural equation modeling (SEM).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This latter study also provided measurements for the elderly and children. The affordability of X-ray, MRI, CT scan, double beam low dose X-ray absorptiometry (DEXA) [ 24 , 25 ], and 3D infrared scanning [ 26 , 27 ], allows for the screening of large cohorts, and for the personalized screening of body sizes, making population studies feasible. The data structures provided by these methods are quite different.…”
Section: Resultsmentioning
confidence: 99%
“…Only relatively recently inertial parameters have been published, in relation to different genders and races [18,19], and norms for Asian men were also provided [20][21][22]. There have been attempts to profile a single state population or special small populations, for example, a study on Bulgarian [23] or Indonesian population which showed very different distributions in dimensions, COM location and inertial parameters of these populations in comparison to Caucasian [24]. In particular, feet and hands showed to be longer in Indonesian men relative to Caucasian men.…”
Section: Modern and Contemporary Timesmentioning
confidence: 99%